Role of ENaC in gender-associated differences in blood pressure - Guo-feng Yu; Li-qin Yu; Qin-rui Lai; Wei Li (Iranian Journal of Basic Medical Sciences)
Objective(s): Sexual dimorphism in blood pressure regulation has been extensively noted in humans, but the underlying mechanisms remain to be fully understood. Our research aims to investigate the possible correlation between gender-associated differences in blood pressure and renal sodium transport. Materials and Methods: We measured male and female mice’s blood pressure, urine, and plasma sodium concentration when fed a regular or high-Na+ diet. After that, their renal sodium transporters were assessed by western blot and immunofluorescence. For further investigation, male mice were castrated to observe the differences in blood pressure and renal sodium transporters compared to normal mice. Results: Male mice exhibited higher blood pressure and lower renal sodium excretion than female littermates. Furthermore, the blood pressure of male mice exhibited a more significant and rapid increase relative to female mice when the diet was switched from control sodium to high sodium. Western blot and immunofluorescent staining revealed that in male mice, the sodium transporters epithelial sodium channel (ENaC) and the upstream kinases SPAK (Ste20-related proline/alanine-rich kinase), OSR1 (oxidative stress response kinase 1), and WNK4 (Lysine-Deficient Protein Kinase 4) were elevated. Beyond that, male mice exhibited lowered blood pressure and reduced abundance of ENaC (α, β, and γ) after castration.Conclusion: ENaC plays a significant role in gender-associated differences in blood pressure and renal sodium reabsorption.